Financial constraints and intangible investments: Do innovative and non-innovative firms differ? - Sandro Montresor; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2019)
We investigate the extent to which financial constraints hamper the firms' investment in intangibles. Drawing on the extant literature, we maintain that a distinction should be kept between innovators and non-innovators. Moreover, we argue that such a distinction should be investigated along the whole spectrum of intangibles firms invest and by addressing the risks of reverse causality and simultaneity bias in the relationship. Through an original quasi-panel extension of a recent European Innobarometer survey, we estimate two sets of recursive bivariate probit models - for innovative and non-innovative firms' investments - from which interesting results emerge. Financial barriers hamper the investment of both kinds of firms only for R&D, design, and organisation and business processes. With respect to other intangibles, instead, financial barriers act only on innovators (or non-innovators) or are even absent. Furthermore, the hampering role of financial barriers distributes differently across different intangibles between innovators and non-innovators.
Keywords: O30; O32; O33; 330; R&D; intangibles; innovation; financial barriers